Protocol for a multi-domain scoping review to identify measures of decision-making ability in an ageing population - Janel Hanmer; Richard Gershon; Sandra Weintraub; Zahra Hosseinian; Emily H. Ho; Berivan Ece; Miriam A. Novack; Sarah Pila; Tatiana Karpouzian-Rogers; Molly A Mather; Elizabeth McManus Dworak; Patricia Bucko; et al. (BMJ Open, 2024)
Introduction Deficits in decision-making (DM) can lead to adverse outcomes across multiple domains such as financial management and medical care. By hindering such DM abilities, cognitive impairment (CI) often affects quality of life. Routine screening for CI, however, does not include systematic and comprehensive assessment of DM ability. While there are many DM measures, there is considerable heterogeneity in what constructs are measured and the populations in which they have been validated. This scoping review protocol details the proposed comprehensive examination of published literature on DM measures used in adults aged 45 years and older.Methods and analysis Arksey and O’Malley’s (2005) scoping review methodology framework will guide the current scoping review. We will systematically search Embase (Elsevier), MEDLINE (Ovid), PsycINFO (Ebsco), Cochrane Library (Wiley), Web of Science (Clarivate) and Scopus (Elsevier) to identify the studies meeting our eligibility criteria. We will review literature published between January 2018 and November 2023. Following best practice recommendations, a two-stage study selection process will be applied. First, titles and abstracts will be independently reviewed by two reviewers based on our eligibility criteria. Second, full texts will be screened and data will be extracted only from the articles included after the full review. The results of the current scoping review will be reported in adherence to PRISMA-Scr guidelines.Ethics and dissemination This study does not require ethics approval as the scoping review methodology involves reviewing results from publicly available published materials. Results of the scoping review will be submitted for publication in a peer-reviewed journal.Trial registration number NIA grant number 1U24AG082022-01.